2020
DOI: 10.1371/journal.pone.0238815
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of strategies using simulation model to control a potential outbreak of highly pathogenic avian influenza among poultry farms in Central Luzon, Philippines

Abstract: The Philippines confirmed its first epidemic of Highly Pathogenic Avian Influenza (HPAI) on August 11, 2017. It ended in November of 2017. Despite the successful management of the epidemic, reemergence is a continuous threat. The aim of this study was to conduct a mathematical model to assess the spatial transmission of HPAI among poultry farms in Central Luzon. Different control strategies and the current government protocol of 1 km radius preemptive culling (PEC) from infected farms were evaluated. The alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…The number of cases only decrease by one, whereas an additional 31 farms were depopulated. Another simulation study based on the transmission kernel function suggested a non-depopulation strategy for low-risk regions [22]. It appears that a standard culling radius is not optimal for poultry premises across the whole country because of variation in the transmission rate and vulnerability to infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of cases only decrease by one, whereas an additional 31 farms were depopulated. Another simulation study based on the transmission kernel function suggested a non-depopulation strategy for low-risk regions [22]. It appears that a standard culling radius is not optimal for poultry premises across the whole country because of variation in the transmission rate and vulnerability to infection.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that local spatial transmission would occur between poultry farms within a spatiotemporal cluster with a high rate of HPAI infections. To test this hypothesis, we derived the force of infection based on a transmission kernel function, in accordance with previous research [8,10,22], as follows:…”
Section: Estimation Of Spatial Transmission Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Most IBMs (16/19; Table 2 ) investigated the transmission process between farms [ 42 , 46 , 47 , 50 , 54 56 , 59 , 61 , 63 , 67 , 70 , 71 , 75 ] or between administrative areas [ 36 , 40 , 50 , 55 ], with two articles evaluating both in the same study [ 50 , 55 ]. The remaining three articles considered transmission at two different scales (e.g., within-farm and between-farms) [ 38 , 60 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…IAV exhibits remarkable genetic and genomic diversity that allows IAV to be both a pandemic and zoonotic threat (Brooke, 2017). Recurrent outbreaks of avian influenza add to mounting concerns of the next potential influenza pandemic (Cowling et al, 2013;Fraser et al, 2009;Salvador et al, 2020;Wang and Palese, 2009). Vaccines targeting influenza viruses must be reformulated annually (Krammer et al, 2018).…”
Section: Ii-b Introductionmentioning
confidence: 99%